Impact of Training on Three-Dimensional versus Two-Dimensional Laparoscopic Systems on Acquisition of Laparoscopic Skills in Novices: A Prospective Comparative Pilot Study. (22nd November 2016) - Noureldin, Yasser A.; Stoica, Ana; Kaneva, Pepa; Andonian, Sero
Abstract : In this prospective educational study, 10 medical students (novices) were randomized to practice two basic laparoscopic tasks from the MISTELS program, namely, Pegboard Transfer (PT) and Intracorporeal Knot Tying (IKT) tasks, using either a 2D or a 3D laparoscopic platform. There was no significant difference between both groups in the baseline assessments (PT task: 130.8 ± 18.7 versus 151.5 ± 33.4; p = 0.35 ) (IKT task: 123.9 ± 41.0 versus 122.9 ± 44.9; p = 0.986 ). Following two training sessions, there was a significant increase in the scores of PT task for the 2D (130.8 ± 18.7 versus 222.6 ± 7.0; p = 0.0004) and the 3D groups (151.5 ± 33.4 versus 211.7 ± 16.2; p = 0.0001). Similarly, there was a significant increase in the scores of IKT task for the 2D (123.9 ± 41.0 versus 373.3 ± 47.2; p = 0.003) and the 3D groups (122.9 ± 44.9 versus 338.8 ± 28.6; p = 0.0005). However, there was no significant difference in the final assessment scores between 2D and 3D groups for both tasks (p > 0.05). Therefore, 3D laparoscopic systems do not provide an advantage over 2D systems for training novices in basic laparoscopic skills.